The design and implementation of an in-application automated testing and evaluation system for computer literacy skills based on the European and international computer driving licence (ECDL/ICDL) - Avgousti, Sotiris; Masouras, Panicos (My University, 2010)
models which, in turn, contributed to the development of the corresponding assessment tools and systems. With the ECDL at the forefront of the international computer literacy skills market and with its important role in the specification of digital literacy agenda, it becomes vitally important to ensure that assessment systems leading to this qualification are of the highest technical and pedagogical quality. This paper presents the experiences gained from the design, testing and implementation of such an assessment system and its deployment in a big-bang approach on a national basis in Cyprus. It explains the system’s technical architecture and components, its functionalities and services and discusses the pedagogical and educational aspects embedded in the design and highlights the pitfalls and lessons learned in the areas of team building and project.
Keywords: Computer skills; Computer literacy; Assessment; Computer assisted testing; Formative; Summative